Eagle Syndrome - Thirsa D. Michiels, MD; Martijn S. Marsman, MD; Andy van Veen, MD, DMD; Patrick W.H.E. Vriens, MD, PhD; Gert-Jan Lauret, MD, PhD; Jan M.M. Heyligers, MD, PhD (JACC: Case Reports, 2020)
Eagle syndrome is a rare aggregate of symptoms caused by an elongated styloid process. We present the unique case of bilateral vascular Eagle syndrome in a patient who experienced a unilateral acute swelling due to bleeding at the level of the right internal carotid artery. This complication has never been described before. (Level of Difficulty: Advanced.)